Feasibility study of reach stacker model choice - Lysak, Serhii; Balaka, Maksym; Riepin, Vladyslav; Yahodynets, Volodymyr; Matsybura, Artem (My University, 2025)
The paper considers an approach to choosing the optimal reach stacker model for container terminals based on engineering-and-economic performance. The technical characteristics of models from leading global manufacturers of handling machinery are analyzed. A methodology to determine the technical and operational productivity of reach stackers in the absence of complete data from the manufacturer is proposed. Five key efficiency criteria are identified: specific power, energy saturation, economic efficiency, cost power and cost mass. The most effective model choice is justified based on the ranking of models for each criterion and the calculation of the final score. The study results can be applied when forming technical requirements and specifications for the purchase of handling machinery. They also serve as an analytical basis for making informed management decisions in the field of logistics infrastructure development, and cargo terminals and ports modernization.
Техніко-економічне обґрунтування вибору моделі річстакера
У роботі розглянуто підхід до вибору оптимальної моделі річстакера для контейнерних терміналів на основі техніко-економічних показників. Проаналізовано технічні характеристики ряду моделей провідних світових виробників перевантажувальної техніки. Запропоновано методику визначення технічної та експлуатаційної продуктивності річстакерів за відсутності повних даних від виробника. Визначено п’ять ключових критеріїв ефективності: питома потужність, енергонасиченість, економічність, вартісна потужність та вартісна маса. На основі ранжування моделей за кожним критерієм та підрахунку підсумкового балу обґрунтовано вибір найефективнішої моделі.
Keywords: reach stacker; container; productivity; efficiency criterion; річстакер; критерій ефективності; продуктивність; контейнер; 621.86